Двощиткові прямокутні накладки в скарбах Подніпров’я VII ст. - Скиба, А.В. (Археологія, 2016)
Статтю присвячено двощитковим прямокутним накладкам поясів, їх типології, території поширення та питанням хронології, а також поясним гарнітурам «геральдичного» стилю, до яких вони входили. Two-paneled rectangular plates (type II-2) are represented mostly by silver casted items. Their absolute majority are related with the 7th century hoards found in the Dnipro River region. They are predominantly spread in the middle flow of the Dnipro River and on its left bank. Outside its region they are represented by single findings in the Oka River region (Yelizavet-Mikhailovka) and in the Crimea (Suuk-Su). This type plates differ from each other mainly by decoration which peculiarities served for distinction of the variants. Today, not less than ten variants can be named. Variant 1 significantly differs from others by number of findings and the area of the spread. It is peculiar with the apertures in shape of a compound cross. They are usually represented in assemblages by the sets of identic items consisting from two to eight (insignificant differences related to the production process are possible). In cases, when reconstruction of belt sets’ completeness is possible, the combination of two-paneled triangular plates with quite settled typological block of belt details can be traced. There are B-shaped buckles with movable panel, shield-shaped and 3-shaped panels, T-shaped plates, as well as belt tips with side openings among them. The issue of chronology of two-paneled rectangular moldings needs the further development. Plates with insets ornamented with granulation, as well as this type plates of two more variants should be referred to the latest examples. Spread of belt sets with the collections of plates of II-2 type, to the author’s opinion, marks the military and political union of the Slavs which existed in the second and third quarters of the 7th century on the territory of the middle flow of the Dnipro River and on its left bank. Двущитковые прямоугольные накладки (тип ІІ-2) в подавляющем большинстве представлены серебряными литыми изделиями. Абсолютное их большинство связано с днепровскими кладами VII в. Основным ареалом их распространения является Среднее Приднепровье и Днепровское Левобережье. За пределами этого региона они представлены единичными находками в Поочье (Елизавет-Михайловка) и в Крыму (Суук-Су). Между собой накладки этого типа отличаются, главным образом, декором, особенности которого послужили для выделения вариантов. На сегодня их насчитывается не менее десяти. По количеству находок и широте распространения существенно выделяется вариант 1, для которого характерны прорези в виде сложного креста. В комплексах они, как правило, представлены комплектами, насчитывающими от двух до восьми идентичных изделий (возможны незначительные отличия, связанные с процессом изготовления). В случаях, когда возможна реконструкция комплектности поясных гарнитуров, прослеживается сочетание двущитковых прямоугольных накладок с достаточно устойчивым типологическим блоком деталей поясов. Среди них В-образные пряжки с подвижным щитком, щитообразные накладки, З-образные накладки, Т-образные бляшки, а также поясные наконечники с боковыми вырезами. Вопрос хронологии двущитковых прямоугольных накладок требует дальнейшей разработки. К наиболее поздним образцам следует отнести накладки со вставками с орнаментами из зерни, а также накладки этого же типа ещё двух вариантов. Распространение поясных наборов с комплектами накладок типа ІІ-2, по нашему мнению, маркирует военнополитическое объединение славян, существовавшее во второй—третьей четвертях VII в. на территории Среднего Приднепровья и Днепровского Левобережья.